2020
DOI: 10.3390/nu12010221
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Timing of Exercise and Eating on Postprandial Response in Adults: A Systematic Review

Abstract: Type 2 diabetes is a major public health concern. Management of this condition has focused on behavior modification through diet and exercise interventions. A growing body of evidence has focused on temporality of dietary intake and exercise and potential effects on health. This review summarizes current literature that investigates the question “how does the timing of exercise relative to eating throughout the day effect postprandial response in adults?” Databases PubMed, Scopus, Cochrane Library, CINAHL, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 37 publications
2
42
0
Order By: Relevance
“…We have shown that a walking prescription can increase self-reported time spent walking. Given the extent to which even modest postprandial physical activity can improve glycaemic control, 12,13 daily physical activity should be a regular topic in consultations with patients with diabetes. Our findings are relevant to all health-care professionals in health-care teams, providing support to increase patient success when following a physical activity prescription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that a walking prescription can increase self-reported time spent walking. Given the extent to which even modest postprandial physical activity can improve glycaemic control, 12,13 daily physical activity should be a regular topic in consultations with patients with diabetes. Our findings are relevant to all health-care professionals in health-care teams, providing support to increase patient success when following a physical activity prescription.…”
Section: Discussionmentioning
confidence: 99%
“…11 A prescription to walk regularly may be more accessible and reduce inequities for patients as it does not incur the monetary cost of class-or gym-based activities, and it may not require travel time to undertake. Given the benefits observed for postprandial glycaemia by people with type 2 diabetes who walk after eating, 12,13 we aimed to identify the barriers and facilitators to adhering with a prescription to walk after each main meal for adults with type 2 diabetes. The findings may provide important context to patients' successes or failures when prescribed regular physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the timing of exercise around meals on postprandial hyperglycemia have been widely discussed. Two reviews discussed a beneficial effect of exercise performed post-meal on impaired postprandial hyperglycemia (Aqeel et al, 2020;Haxhi et al, 2013), but inconsistent results were also obtained. For example, in previous studies comparing the effects of exercise performed pre-and post-meal in subjects with diabetes, postprandial hyperglycemia was suppressed by post-meal exercise alone (Colberg et al, 2009;Ruegemer et al, 1990), or pre-meal exercise alone (Terada et al, 2016), or both preand post-meal exercise (Heden et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The timing of exercise critically affects energy metabolism, clock gene expression, and muscle protein synthesis (Aoyama & Shibata, 2017, 2020; Aqeel et al, 2020; Haxhi et al, 2013). Fat oxidation over 24 h is increased by exercise performed before breakfast, but not after breakfast and the subsequent period (Iwayama et al, 2017; Iwayama, Kawabuchi, et al, 2015; Iwayama, Kurihara, et al, 2015; Shimada et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We would like to submit the following corrections to our recently published paper [1] after discovering the inclusion of three studies in our review that did not meet the inclusion criteria we had specified in our methods: healthy adults (≥18 years old) or individuals with overweight/obesity and/or type 2 diabetes (T2D). Specifically, all three studies included participants with type 1 diabetes (T1D) which was part of our exclusion criteria as described in our manuscript.…”
mentioning
confidence: 99%